カナダ ホッキョクケン エンガン ノ リクスイイイキ デ エタ ケイソウ Navicula sensu lato ノ ブンルイガクテキ ケントウ - 福島, 博; フクシマ, ヒロシ; 木村, 努; キムラ, ツトム; 小林, 艶子; コバヤシ, ツヤコ; 福嶋, 悟; フクシマ, サトル; 吉武, 佐紀子; ヨシタケ, サキコ; Fukushima, Hiroshi; Kimura, Tsutomu; et al. (2012)
P(論文) 1997年7-8月に,アムンゼンが航海した北西航路の逆コースの航海に参加した.その時に寄港したHerschel Isl.,Smoking Hills,Holman,Byron BayおよびCambridge Bayで採集した珪藻サンプルを基に,Navicula sensu latoに属す35 taxaを同定した.その内訳は Navicula 20 taxa,Chamaepinnularia 4 taxa,Craticula,Placoneis各2 taxa,Aneumatus,Caloneis,Fallacia,Naviculadicta,Parlibellus,Pinnuavis,Sellaphora各1 taxonである.これらの珪藻には分布上,広汎性種とされている種,北方性・山岳性種とされている種と,この地域の固有種が混在している.また,今回調査したのはすべて陸水域であるにもかかわらず,淡水性種,汽水性種,海産種が混在している.上記の混在率は緯度,地形,陸水域の位置などによって異なる.陸水域であるにもかかわらず汽水性種,海洋性種が見られるのは,風送塩による陸水域の鹹水(かんすい)化が原因と推察できる.今回,次に示す七つの新組み合わせを行う.Chamaepinnularia soeherensis (Krasske) Lange-Bert. & Krammer var. hassiaca (Krasske) H. Fukush. et al.Chamaepinnularia soeherensis (Krasske) Lange-Bert. & Krammer var. inflata (Krasske) H. Fukush. et al.Chamaepinnularia soeherensis (Krasske) Lange-Bert. & Krammer var. linearis (Krasske) H. Fukush. et al.Chamaepinnularia soeherensis (Krasske) Lange-Bert. & Krammer var. muscicola (J.B. Petersen) H. Fukush. et al.Placoneis amphibola (Cleve) E.J. Cox var. amphibola f. alaskensis (Foged) H. Fukush. et al.Placoneis amphibola (Cleve) E.J. Cox var. amphibola f. rectangularis (Foged) H. Fukush. et al.Placoneis amphibola (Cleve) E.J. Cox var. arctica (R.Patrick & Frese) H. Fukush. et al. We identified 35 taxa of Navicula sensu lato in materials from inland waters at Herschel lsland, Smoking Hills, Holman, Byron Bay and Cambridge Bay while sailing across the reverse course of the Northwest Passage in July and August 1997. We found 20 taxa of Navicula, 4 of Chamaepinnularia, 2 each of Craticula and Placoneis, and 1 each taxon of Aneumatus, Caloneis, Fallacia, Naviculadicta, Parlibellus, Pinnuavis, and Sellaphora. The materials contain cosmopolitan species intermingled with subalpine or mountain species and endemic species (Table 1). Although samples were collected from inland waters, brackish or marine species (see Table 1) were mixed with fresh-water species similar to those reported from Antarctica. The occurrence of brackish-water and marine species is though to be made ...